2018
DOI: 10.1515/gmj-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and sufficient condition for the boundedness of the Gegenbauer–Riesz potential on Morrey spaces

Abstract: In this paper, we study the Riesz potential (G-Riesz potential) generated by the Gegenbauer differential operator G_{\lambda}=(x^{2}-1)^{\frac{1}{2}-\lambda}\frac{d}{dx}(x^{2}-1)^{\lambda+% \frac{1}{2}}\frac{d}{dx},\quad x\in(1,\infty),\,\lambda\in\Bigl{(}0,\frac{1}{2% }\Bigr{)}. We prove that the G-Riesz potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…4], it was shown that, for 𝛼 ≥ 2𝜆 + 1 and for 𝑓 ∈ L p,𝜆 (R + ) , I 𝛼 G does not exist. In [17] for the G-Riesz potential I 𝛼 G on G-Morrey space, the following theorem is proved by analogue of the Theorem 1.1.…”
Section: Definitions Notations and Auxiliary Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…4], it was shown that, for 𝛼 ≥ 2𝜆 + 1 and for 𝑓 ∈ L p,𝜆 (R + ) , I 𝛼 G does not exist. In [17] for the G-Riesz potential I 𝛼 G on G-Morrey space, the following theorem is proved by analogue of the Theorem 1.1.…”
Section: Definitions Notations and Auxiliary Resultsmentioning
confidence: 97%
“…Let Hr=false(0,rfalse)normalℝ+.$$ {H}_r&#x0003D;\left(0,r\right)\subset {\mathrm{\mathbb{R}}}_{&#x0002B;}. $$ Next, we need the following relation (see [16, 17]) ||Hrλ=true∫0rsh2λtdt()shr2γ,$$ {\left&#x0007C;{H}_r\right&#x0007C;}_{\lambda }&#x0003D;\int_0&#x0005E;rs{h}&#x0005E;{2\lambda } tdt\approx {\left( sh\frac{r}{2}\right)}&#x0005E;{\gamma }, $$ where γ=γλfalse(rfalse)={centerarray2λ+1,if0<r<2,array4λ,if2r<,$$ \gamma &#x0003D;{\gamma}_{\lambda }(r)&#x0003D;\left\{\begin{array}{c}2\lambda &#x0002B;1,\kern3.0235pt \mathrm{if}\kern6.05pt 0&lt;r&lt;2,\\ {}4\lambda, \kern9.07pt \mathrm{if}\kern0.1em \hspace{6.05pt}2\le r&lt;\infty, \end{array}\right. $$ and 0<λ<12$$ 0&lt;\lambda &lt;\frac{1}{2} $$.…”
Section: Definitions Notations and Auxiliary Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gegenbauer differential operator was introduced in [5]. For the properties of the Gegenbauer differential operator, we refer to [3,4,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%